Methods to estimate premorbid intelligence - Karakuła, Hanna; Stecka, Mariola; Pawełczak, Paweł (Current Problems of Psychiatry, 2012)
In the patient’s neuropsychiatric assessment it is important to evaluate the premorbid intelligence functioning. The aim of this study was the review of the methods used in estimating premorbid IQ and the evaluation of their reliability. Those methods were divided into four thematic groups concerned: with demographic variables, Wechsler’s scale WAIS-R, verbal tests and combination of various methods. This review allows choosing methods for the estimation of premorbid IQ, which can be useful in theory and in practice, during the formation of rehabilitation and treatment programs for patients with decline in intellectual functioning, caused by morbidity factors.